Phylogeographic diversification of antelope squirrels (Ammospermophilus) across North American deserts. (23rd April 2013) - Mantooth, Stacy J.; Hafner, David J.; Bryson, Robert W.; Riddle, Brett R.
Abstract : We investigated the biogeographic history of antelope squirrels, genus Ammospermophilus, which are widely distributed across the deserts and other arid lands of western North America. We combined range‐wide sampling of all currently recognized species of Ammospermophilus with a multilocus data set to infer phylogenetic relationships. We then estimated divergence times within identified clades of Ammospermophilus using fossil‐calibrated and rate‐calibrated molecular clocks. Lastly, we explored generalized distributional changes of Ammospermophilus since the last glacial maximum using species distribution models, and assessed responses to Quaternary climate change by generating demographic parameter estimates for the three wide‐ranging clades of A. leucurus . From our phylogenetic estimates we inferred strong phylogeographic structure within Ammospermophilus and the presence of three well‐supported major clades. Initial patterns of historical divergence were coincident with dynamic alterations in the landscape of western North America, and the formation of regional deserts during the Late Miocene and Pliocene. Species distribution models and demographic parameter estimates revealed patterns of recent population expansion in response to glacial retreat. When combined with evidence from co‐distributed taxa, the historical biogeography of Ammospermophilus provides additional insight into the mechanisms that impacted diversification of arid‐adapted taxa across the arid lands of western North America. We propose species recognition of populations of the southern Baja California peninsula to best represent our current understanding of evolutionary relationships among genetic units of Ammospermophilus . © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 949–967.